Socialization Of Problem-Based Learning Model With Reading, Questioning, And Answering (PBLRQA) In Empowering Student Retention - Usman, Ali; Hatip, Moch.; Widiyanto, Wahyu Eko; Natasha, Meita Aruri; Fajriyah, Alifia Iffah (JIWAKERTA: Jurnal Ilmiah Wawasan Kuliah Kerja Nyata, 2025)
Student retention is an important aspect that needs to be considered in the learning process, because it ensures that the knowledge gained can be stored for a long time and reused when required. Therefore, current learning must prioritize empowering student retention as part of a strategy to improve the quality of education. This community service aims to socialize the PBLRQA learning model to empower student retention. The method of implementing the activity consists of two main stages: (1) workshop and (2) mentoring the implementation of the learning model. The workshop focuses on understanding the role of retention in learning and how to improve it. Meanwhile, mentoring the implementation of the PBLRQA model is carried out through classroom learning practices, where teachers are directly assisted in implementing this model. The workshop results showed that teachers who were actively involved in the discussion better understood the importance of retention in learning. Furthermore, the results of mentoring the implementation of the PBLRQA learning model indicated that teachers had understood how to apply this model in the classroom. Moreover, they stated that the PBLRQA model has great potential in improving student retention. Teachers have also understood the concept of retention, including its meaning, its role in learning, and how to measure and improve student retention. In addition, teachers have become familiar with one of the learning models that can support increasing student retention, namely the PBLRQA learning model, along with its application in the learning process.